Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5369/jsst.2012.21.2.144
|View full text |Cite
|
Sign up to set email alerts
|

The Design of Temporal Bone Type Implantable Microphone for Reduction of the Vibrational Noise due to Masticatory Movement

Abstract: A microphone for fully implantable hearing device was generally implanted under the skin of the temporal bone. So, the implanted microphone's characteristics can be affected by the accompanying noise due to masticatory movement. In this paper, the implantable microphone with 2-channels structure was designed for reduction of the generated noise signal by masticatory movement. And an experimental model for generation of the noise by masticatory movement was developed with considering the characteristics of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This configuration has also been mentioned in some patents [ 59 , 60 ]. A possible arrangement of two ECMs into a single unit, presented in a subsequent study [ 61 ], is shown in Fig. 4 .…”
Section: Description Of Implantable Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This configuration has also been mentioned in some patents [ 59 , 60 ]. A possible arrangement of two ECMs into a single unit, presented in a subsequent study [ 61 ], is shown in Fig. 4 .…”
Section: Description Of Implantable Sensorsmentioning
confidence: 99%
“…3 Carina parts of TIHA Carina (Adapted from [ 48 ], available from PubMed Central)
Fig. 4 Subcutaneous microphones scheme of combined subcutaneous microphones (Adapted from [ 61 ], available from Korea Institute of Science and Technology Information)
…”
Section: Description Of Implantable Sensorsmentioning
confidence: 99%